(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Fine motor development is an essential aspect of preschool children’s readiness for learning. In the digital era, reduced engagement in manipulative play activities due to excessive gadget use may hinder children’s fine motor development. This study aimed to determine the effect of collage play therapy on the fine motor development of preschool-aged children. A quantitative approach with a quasi-experimental design using a non-equivalent control group design was employed. The sample consisted of 20 respondents, including 10 children in the intervention group and 10 children in the control group, selected through purposive sampling. Data were collected through observation and analyzed using the Wilcoxon and Mann–Whitney tests. The results showed a significance value of 0.004 (p < 0.05), indicating that collage play therapy had a significant effect on improving children’s fine motor development. Collage play therapy proved to be an effective, simple, and enjoyable stimulation method for supporting preschool children’s development. The limitations of this study include the relatively small sample size and the implementation of the study in a single location. Future research is recommended to involve a larger sample and a wider geographical coverage to enhance the generalizability of the findings